Psychodynamic Therapist’s Subjective Experiences With Remote Psychotherapy During the COVID-19-Pandemic—A Qualitative Study With Therapists Practicing Guided Affective Imagery, Hypnosis and Autogenous Relaxation - Jesser, Andrea; Muckenhuber, Johanna; Lunglmayr, Bernd (Frontiers in Psychology, 2022)
The COVID-19-pandemic brought massive changes in the provision of psychotherapy. To contain the pandemic, many therapists switched from face-to-face sessions in personal contact to remote settings. This study focused on psychodynamic therapists practicing Guided Affective Imagery, Hypnosis and Autogenous Relaxation and their subjective experiences with psychotherapy via telephone and videoconferencing during the first COVID-19 related lockdown period in March 2020 in Austria. An online survey completed by 161 therapists produced both quantitative and qualitative data with the latter being subject to a qualitative content analysis. Our research suggests that telephone and videoconferencing are considered valuable treatment formats to deliver psychodynamic psychotherapy. However, therapists’ experiences with remote psychotherapy are multifaceted and ambiguous. In particular, the findings raise questions concerning the maintenance of the therapeutic alliance, the development of the analytic process, the sensitivity to unconscious communication, and the indication for certain types of patients that still need further investigation. Our research indicates that the long-standing reticence towards remote treatments offers among psychodynamic therapists is becoming more differentiated and partially dissolves as therapists gain experiences in their use. Attitudes are becoming more open. At the same time, the way is being prepared to take a closer look at the specific processes and dynamics of remote psychotherapy and to examine them critically in future studies.